HAPPINESS PERCEPTIONS OF PRESCHOOLERS AND PARENTAL STRATEGIES USED TO INCREASE CHILDREN’S HAPPINESS - Eminanç, Çiçek; Tarman, Ilknur (International Journal of Child, Youth and Family Studies, 2025)
This qualitative research study aimed to evaluate how preschoolers aged 4 to 5 perceived “happiness” and the strategies parents use to make their children happier. The criteria sampling approach, a purposeful sampling technique, was utilized to create the study group, which included 20 preschoolers and their parents who had applied for assessment by the Child Development Polyclinic of a maternity and pediatrics hospital in Istanbul, Türkiye. Apart from demographic information, the data employed in the study comprised semi-structured interviews and children’s descriptions of their drawings; these were analyzed using content analysis. The study’s findings showed that the children used adjectives that express positive emotions, such as “laughing”, “joyful”, and “loving”, to describe their feelings, and were reported being happy when they engaged in play-based activities such as playing video games, watching television, engaging in sports, and visiting the beach or the park. The children’s picture drawings of happiness mostly featured aspects of play and nature. One of the research’s most significant results is that parents employed a variety of methods to make their children happy, like playing games, taking them on walks, taking them to the park, and cooking their desired foods. The article concludes with suggestions based on the findings obtained from the research.